Atlas of Woody Plants in China Distribution and Climate - Fang, Jingyun; Wang, Zhiheng; Tang, Zhiyao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"Atlas of Woody Plants in China: Distribution and Climate(3y (Bdocuments the spatially-explicit county-level distribution of all 11,405 woody plants in China, together with life form information for most species. It also provides climate information for each species, with the county-level average and range of 12 climatic indices and of vegetation net primary productivity. It is the first and largest comprehensive atlas in the world for the distribution of China$1 (Bs plants and was compiled on the basis of almost all related literature published throughout China. The atlas should serve as an indispensable handbook for all those who are interested in the plants, ecology, geography, environment, horticulture, and silviculture of China and East Asia. Dr. Jingyun Fang is a Cheung Kong Professor at the Department of Ecology, Peking University, China. Dr. Zhiheng Wang and Dr. Zhiyao Tang are both ecologists working at the same institute.s
Introduction to the Compilation of This Atlas -- Characteristics of Distribution of Woody Plants in China -- Climatic Variables and Their Distribution in China -- Species Distribution and Climates.
Keywords: Life sciences; Agriculture; Ecology; Applied Ecology; Botany; Nature Conservation; Life Sciences; Plant Systematics/Taxonomy/Biogeography.; Applied Ecology; Nature Conservation; Ecology; Plant Sciences; Agriculture